Use of Synonyms, Antonyms and Own Vocabulary in Television Captions - Isokulov Abdullo Oblokul Ogli (Genius Journals, 2023)
The importance of the audience on television, the choice of television viewers, and the intensity of competition for ratings require improvement in the script of television programs and the viewership. The content of a television program script directly depends on the dictionary meaning of the words used in them and the variety of content. This ensures that the main place on television is occupied by television programs created taking into account the existence of differences between common and literary language. In this case, synonyms, antonyms and words from own vocabulary are of great importance.
Keywords: synonym; antonym